Academic Tillage: Positive Impact of the Rural Education Division in the Development of Rural and Indigenous Communities - Vargas-Morales, Marielos (2015)
Through a metaphor about what planting involves, this essay seeks to reflect on the work and achievements of the Rural Education Division (División de Educación Rural or DER) at the University of Costa Rica. To do this, the article looks in retrospect some important actions that DER has developed, not only to advise about its uprising and consolidation as an academic unit, but to identify those impacts which are significant, that have provided university projection and recognition at national level by addressing the needs of rural and indigenous populations in vulnerability conditions.